Studies on Incompatibility Pollination and Floral Morphological Polymorphism of Carambola (Averrhoa Corambola L) - Fushimi, Nobuhiko (1998)
The objectives of this study were to elucidate the physiological basis of selfincompatibility system and the floral morphological polymorphism in carambola (Averrhoa carambola L.). Within 30 minutes after pollination, pollen degradation and hydration commenced on the stigma surface. Pollen tubes subsequently emerged from colpal furrow and crawled into apertures of vesicles. The pollen tubes reached the base of the transmitting tract of the style on legitimate pollinations in pin and thrum morphs at 8.0 h after pollinations. Pollen tubes were uniformly inhibited at the middle of the style in pin illegitimate pollinations, however, tubes occasionally penetrated to the base of the transmitting tract of the style. futhrum illegitimate pollinations, tubes were inhibited at the junction between stigmatic and stylar tissues. Result of illegitimate pollination confirmed the partial loss of incompatibility in pin as opposed to the strong incompatibility in thrum as shown by both fluorescence microscopic observation and the field controlled pollinations study. Ripen fruits from pin illegitimate pollinations were significantly smaller and contained less seed compared to legitimate pollinations. Carambola flower consisted of 5 rose-pink sepals, a pistil, 5 stamens and 5 staminoids. Pistil length was significantly longer in pin than in thrum morphs. On the other hand, the stamen length was significantly longer in thrum than in pin morphs. Pollen grain shape of pin and thrum morphs was oblate spherical and tricolporate. Pollen diameter was significantly larger in thrum than in pin morphs. Foveolate pattern of pollen exine sculpturing was more intense in pin than in thrum morphs. Each of the five stylar tissues terminated in a capitate stigma. The stigma receptive surface surrounded the stylar tip, except for a strip along the abaxial part between the middle and base of stylar tissues. Vesicle was a dewdrop-shaped cell. Stigma and vesicles sizes were significantly greater in pin than in thrum morphs. Result of measurements of the various floral morphological parts revealed highly significant variations even among the various clones within the same morphs.